Early glenohumeral arthritis in the competing athlete - Reineck, J. R.; Krishnan, S. G.; Burkhead, W. Z. (Clinics in Sports Medicine, 2008)
Early glenohumeral degeneration is, at best, a difficult condition for the competing athlete. This is especially true of athletes who participate in overhead sports of baseball, tennis, swimming, and volleyball. However, competitors in football, basketball, and soccer may also find themselves saddled with severe posttraumatic, post-reconstruction, or primary cartilage loss in their shoulders. Unfortunately, this may lead to impeded performance, and, ultimately, derailed careers.